Epileptic phenotypes, electroclinical features and clinical characteristics in 17 children with anti-NMDAR encephalitis. (May 2017) - Haberlandt, E.; Ensslen, M.; Gruber-Sedlmayr, U.; Plecko, B.; Brunner-Krainz, M.; Schimmel, M.; Schubert-Bast, S.; Neirich, U.; Philippi, H.; Kurleman, G.; Tardieu, M.; Wohlrab, G.; et al.
Abstract: Background: Anti-N-methyld -aspartate receptor (NMDAR) encephalitis is a rare disorder characterized by seizures, neuropsychiatric symptoms, dyskinesia and autonomic instability. Objective: Aim of the present study was to evaluate the seizure phenotypes and electroencephalogram (EEG) features in children with anti-NMDAR encephalitis. Methods: Seizure types, electroclinical features and clinical characteristics of 17 children with anti-NMDAR encephalitis were analysed in a retrospective case series from nine centres in Europe. Results: Nearly half (8/17) of the children presented with psychiatric symptoms, whereas in 4/17 patients seizures were the first symptom and in 5/17 both symptoms occurred at the same time. During the following course seizures were reported in 16/17 children. The first EEG detected generalized slowing in 11/17 patients, focal slowing in 3/17 and normal background activity in only 3/17 children. The extreme delta brush (EDB) pattern was detected in 9/17 (53%) patients. Conclusion: In addition to psychiatric symptoms, children with anti-NMDAR encephalitis often show generalized slowing in EEG with or without seizures at initial presentation. EDB is present in half of all children and is potentially a helpful tool for early detection of this immune-mediated disease. Highlights: Children with anti-NMDAR encephalitis may have generalized slowing in EEG with or without seizures at initial presentation. Anti-NMDAR encephalitis diagnosis to be considered in children with psychiatric symptoms and generalized EEG slowing. EDB is present in half of children, therefore may be a helpful tool for early detection of this immune mediated disease.